Impact of the 2012 extreme drought conditions on private well owners in the United States, a qualitative analysis. (December 2016) - Murti, Michelle; Yard, Ellen; Kramer, Rachel; Haselow, Dirk; Mettler, Mike; McElvany, Rocky; Martin, Colleen
Abstract Background Extreme hot and dry weather during summer 2012 resulted in some of the most devastating drought conditions in the last half-century in the United States (U.S.). While public drinking water systems have contingency plans and access to alternative resources to maintain supply for their customers during drought, little is known about the impacts of drought on private well owners, who are responsible for maintaining their own water supply. The purpose of this investigation was to explore the public health impacts of the 2012 drought on private well owners' water quality and quantity, identify their needs for planning and preparing for drought, and to explore their knowledge, attitudes, and well maintenance behaviors during drought. Methods In the spring of 2013, we conducted six focus group discussions with private well owners in Arkansas, Indiana, and Oklahoma. Results There were a total of 41 participants, two-thirds of whom were men aged 55 years or older. While participants agreed that 2012 was the worst drought in memory, few experienced direct impacts on their water quantity or quality. However, all groups had heard of areas or individuals whose wells had run dry. Participants conserved water by reducing their indoor and outdoor consumption, but they had few suggestions on additional ways to conserve, and they raised concerns about limiting water use too much. Participants wanted information on how to test their well and any water quality issues in their area. Conclusions This investigation identified information needs regarding drought preparedness and well management for well owners.